Physico-chemical characteristics of olive leaves and fruits and their relation with Bactrocera oleae (Rossi) cultivar oviposition preference - Malheiro, Ricardo (2018)
Bactrocera oleae (Rossi) (Diptera: Tephritidae) oviposition preference to Portuguese olive cultivars with different susceptibilities (cvs. Cobrançosa, Madural, and Verdeal Transmontana) was studied by physical and chemical parameters. Physical parameters, maturation indices, infestation levels, and fatty acids profiles were recorded.Verdeal Transmontana olives revealed higher susceptibility to olive fly attack, while cv. Cobrançosa was the less affected cultivar. A faster maturation in cv. Cobrançosa and a slower one in cv. Verdeal Transmontana were observed. Verdeal Transmontana olives reported higher volume and lower elongation, while both olives and leaves reported higher lightness, all possible attractive cues for olive fly. Fatty acids composition revealed a characteristic profile in each cultivar with constant differences during crop season.Overall, maturation process influenced biometrical data and color of olive cultivars. The slower maturation process characteristic from cv. Verdeal Transmontana could modulate the composition and physical appearance of olives, therefore interfering with olive fly females oviposition preference.